(untitled) (Theatrum historiae, 2015)
The article explores credit relations among the inhabitants of the three small serfdom towns of the Pardubice estate (Bohdaneč, Dašice, Týnec n. L.) in the 17th century. It primarily focuses on the period of the Thirty Years` War (1620–1650) and tries to find some of its specific features. It pays attention to the intensity of credit relations, the composition of the creditors and their share in the credit and the composition of debts according to the purpose for which they arose. On the basis of the real estate prices, it tries to find out their current economic status and the level of indebtedness by common debts.